Hubungan antara Grit dengan Subjective Well-Being pada Guru Honorer - Ester Hestiningsih; Ratriana Y. E. Kusumiati (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This study aims to determine the relationship between grit and subjective well-being in honorary teachers. The hypothesis proposed is that there is a significant positive relationship between grit and subjective well-being in honorary teachers. The research subjects were 87 people. Data collection used the grit scale compiled by Duckworth (2009), the Satisfaction With Life Scale (SWLS) compiled by Diener, Emomons, Larsen, & Griffin (1985), and The Scale of Positive and Negative Experience (SPANE) compiled by Diener (2009). Data analysis using Pearson product moment correlation method. The results showed that there was a significant positive relationship between grit and subjective well-being (rxy = 0.421; p<0.05). This means that the higher the grit level, the higher the subjective well-being of honorary teachers, and vice versa.